Online Business Training in Marketplace for Beginner for Students of SMA Muhammadiyah 3 Surabaya - Dira Ernawati; Tranggono (Future Science)
Current technological developments provide opportunities for the business world to develop very quickly. One of them is the increasingly widespread online business by utilizing the internet to conduct transactions and promotions. An online business can be an option for building a business. In the 2013 education curriculum, entrepreneurship is taught to all high school students to foster an entrepreneurial spirit from an early age. To support this government program and take advantage of the technological ease of communication devices and the internet, basic training in doing online business is carried out using only gadget devices that are very close to our daily lives. The purpose of this training is not only to bear young entrepreneurs but also to encourage students to do productive activities by utilizing student gadgets to starting an online business. The training was held at SMA Muhammadiyah 3 Surabaya with 45 participants. This training activity uses survey methods, lectures, and guided to create an account at Tokopedia. The target in this activity includes students being able to start a useful activity by doing online business using their gadget devices. Also, students can become graduates who have business skills that can create new jobs.